2015
DOI: 10.5005/jp-journals-10035-1031
|View full text |Cite
|
Sign up to set email alerts
|

To Study the Antimicrobial Stewardship Program in a Large Tertiary Care Teaching Center

Abstract: Introduction As antimicrobial resistance continues to increase and new antimicrobial development stagnates, antimicrobial stewardship programs are being implemented worldwide. The goal of antimicrobial stewardship is to optimize antimicrobial therapy with maximal impact on subsequent development of resistance. Thirty to fifty percent of hospitalized patients receive antimicrobial therapy. Previous data suggest that inappropriate use results in higher mortality rates, longer lengths of stay, and increased medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Cephalosporins were the most commonly implicated antibiotic class in DRPs (27.67%), followed by nitroimidazoles (25.63%). This was consistent with the findings of a few Ethiopian studies (1)(2)(3)(4)(5)(6)(7)(8) . This is quite understood as cephalosporins and nitroimidazoles play a major role in surgical prophylaxis.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Cephalosporins were the most commonly implicated antibiotic class in DRPs (27.67%), followed by nitroimidazoles (25.63%). This was consistent with the findings of a few Ethiopian studies (1)(2)(3)(4)(5)(6)(7)(8) . This is quite understood as cephalosporins and nitroimidazoles play a major role in surgical prophylaxis.…”
Section: Resultssupporting
confidence: 92%
“…However, it is deplorable that approximately half of the patients receive antibiotics unnecessarily or inappropriately as a result of inappropriate prescription for antibiotic prophylaxis, the continuation of empirical therapy in stable patients, although cultures show no bacterial growth and unawareness about the patterns of susceptibility of common pathogens. Inappropriate use of antibiotics paves the way for Drug-Related Problems (DRPs), Surgical Site Infections (SSIs), morbidity, mortality, and antibiotic resistance, thereby increasing the cost of treatment and hospital stay (4)(5)(6)(7)(8) . Literature reviews concerning DRPs indicated that among the medications prescribed in the surgery ward, antibiotics contributed the most (73.8%) towards DRPs (1) .…”
Section: Introductionmentioning
confidence: 99%